A smart vision inspection system on step-NC machine with IOT Environment - Mohammed Saif, Yazid Abdullsameea (2022)
Manufacturing metrology is an imperative part of the sophisticated Industrial 4.0-based manufacturing industry. The Vision Inspection System (VIS) of the modern inspection industry is intelligent, broadly associated and flexible. They are completely adaptable, independent and attainable based on the Internet of Things (IoT) environment. The challenges in this issue stemmed from a lack of adequate and appropriate inspection systems. Accordingly, the lighting framework concentrates on these matters top to bottom to further develop lighting capability. The camera and lighting system were utilized to guarantee product quality. Indeed, even light, distance, coordination with camera and lens, angle of illumination and running, and upkeep costs are a portion of the 3SMVI system critical reasonable issues. It's memorable crucial that the camera doesn't involve the ambient light detected by a light meter in a scene. Nonetheless, the camera sees how much-mirrored light from objects in a scene, is impacted by reflectivity levels. This study proposed an approach to develop an automated smart system based on STEP-NC for Machine Vision Inspection with Internet of Things architecture. Case studies were measured with a 3SMVI system and a Coordinate Measuring Machine (CMM). Based on the results of the case studies, the findings were divided into three sections: First, the developed vision system successfully detected surface feature shape, measured the surfaces after machining the Part in the CNC machine, and the data flow appeared in cloud server-based MQTT protocol, and through an integrated with Open CV platform vision inspection system-based on IoT architecture with STEP-NC based Open CNC. Second, the reading of the roundness data between the 3SMVI system measuring and CMM inspections is more accurate for the CMM which takes more time than the new 3SMVI system which takes less time. Third, the data examination utilized the mean and standard error between the 3SMVI system and the CMM based on hole diameters, which measured roundness according to the data, for the validation of the measurement systems. Thus, the CMM model's standard errors were determined to be lower than the 3SMVI model's common errors.